Genomic heterozygosity and hybrid breakdown in cotton (Gossypium): different traits, different effects. Issue 1 (December 2016) - Dai, Baosheng; Guo, Huanle; Huang, Cong; Zhang, Xianlong; Lin, Zhongxu
Abstract Background Hybrid breakdown has been well documented in various species. Relationships between genomic heterozygosity and traits-fitness have been extensively explored especially in the natural populations. But correlations between genomic heterozygosity and vegetative and reproductive traits in cotton interspecific populations have not been studied. In the current study, two reciprocal F2 populations were developed usingGossypium hirsutum cv. Emian 22 andG. barbadense acc. 3– 79 as parents to study hybrid breakdown in cotton. A total of 125 simple sequence repeat (SSR) markers were used to genotype the two F2 interspecific populations. Results To guarantee mutual independence among the genotyped markers, the 125 SSR markers were checked by the linkage disequilibrium analysis. To our knowledge, this is a novel approach to evaluate the individual genomic heterozygosity. After marker checking, 83 common loci were used to assess the extent of genomic heterozygosity. Hybrid breakdown was found extensively in the two interspecific F2 populations particularly on the reproductive traits because of the infertility and the bare seeds. And then, the relationships between the genomic heterozygosity and the vegetative reproductive traits were investigated. The only relationships between hybrid breakdown and heterozygosity were observed in the (Emian22 × 3–79) F2 population for seed index (SI) and boll number per plant (BN). The maternal cytoplasmic environment may have a significant effect on genomic heterozygosity and on correlations between heterozygosity and reproductive traits. Conclusions A novel approach was used to evaluate genomic heterozygosity in cotton; and hybrid breakdown was observed in reproductive traits in cotton. These findings may offer new insight into hybrid breakdown in allotetraploid cotton interspecific hybrids, and may be useful for the development of interspecific hybrids for cotton genetic improvement.